On the prospects of a logical-semantic approach to creating a code for artificial thinking - Kocharyan, Karen; Lapis, Włodzimierz (Lingua Posnaniensis, 2024)
This article substantiates the practical possibility of modeling the information component of thinking using modern computer technologies, providing programmers with a code diagram of general artificial thinking for familiarization. The rationale for the approach is based on the ideas of the theory of knowledge, philosophy and methodology of language. Attention is paid to the discussion of some provisions of the criticism of artificial systems of thought.